IMPLEMENTASI KOLASE DALAM MENGEMBANGKAN KREATIVITAS ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK HABIBI PARIAMAN - Nelly, Erlinda; Mayar, Farida (Ensiklopedia of Journal, 2020)
This study aims to determine the development of creativity that children can develop through the application of collage activities. The type of collage used is collage that uses natural ingredients. This research was carried out in the Habibi Pariaman Kindergarten. The population in this study were all children in the Habibi Pariaman Kindergarten and the samples used were 5 children in the Habibi Pariaman Kindergarten. The analysis technique used is purposive sampling which is done through the application of collage activities in school learning activities. The results showed that children's artistic abilities can be stimulated through the implementation of collage activities in school. Through collage activities, children look very enthusiastic in developing their artistic abilities and creativity. It is recommended that PAUD teachers use collage activities using natural media to enhance their creativity abilities.